Elimination of cervical cancer in low‐ and middle‐income countries: Inequality of access and fragile healthcare systems. Issue 1 (11th December 2020) - Vale, Diama B.; Teixeira, Julio C.; Bragança, Joana F.; Derchain, Sophie; Sarian, Luis O.; Zeferino, Luiz C.
Abstract: In 2018, WHO called for global action to eliminate cervical cancer. The complexity of the processes involved in terms of prevention is often underestimated. Low‐ and middle‐income countries do not have a robust healthcare framework to ensure high‐quality programs. The present article discusses how fragile healthcare systems are barriers to eliminating cervical cancer, and also reports the experience of a Brazilian prevention program. The article considers how cervical cancer can be interpreted as an indicator of inequality: how women's attitudes and access to care determine an early or late diagnosis, and how strategies combining vaccine and DNA‐HPV tests are crucial. New vaccine schemes, the critical analysis of local data, strengthening communication, managing sentinel events, and integrating vaccination and screening data for the health information system are some of the key activities to sustainable improvement in both access and quality of care. Abstract : There is an urgent need to expand access and quality of care of cervical cancer vaccine and screening in low‐ and middle‐income countries.